Pengaruh Customer Relationship Management terhadap Kepuasan Pelanggan UMKM Kole-Koleh Anggraini pada Masa Pandemi - Golan Hasan; Yang Songsen Samuel; Lilis Cinthya; Karina Rusyen; Martasya Martasya; Ryan Prastama; Kevin Tjoa (STIE AMKOP, 2023)
The purpose of this research is to identify and analyze the customer relationship management framework that was applied by the UKM Kole-Koleh Anggraini during the pandemic. The problems that occur in MSMEs are decreased income, decreased demand, delivery and logistics, limited resources and uncertainty about the future. The method used in this research is observation or survey and the CRM framework. The results of the study show that the CRM framework that has been implemented in SMEs is customer identification, interaction management, service personalization, complaint management, customer data analysis and SWOT analysis. There are several deficiencies in the CRM framework, namely the existence of implementation costs, limited internal resources and a lack of employee involvement and acceptance. Recommendations that can be given to MSMEs to improve customer relations and business management are the use of CRM frameworks such as HubSpot CRM, Zoho CRM, Sales force Essentials and Pipe Drive. Keywords: customer relationship management; pandemic; MSMEs; loyalty